Clock gene daily profiles and their phase relationship in the rat suprachiasmatic nucleus are affected by photoperiod - Sumová, Alena; Jác, Martin; Sládek, Martin; Sauman, Ivo; Illnerová, Helena (Journal of biological rhythms, 2003)
Rhythmicity of the rat suprachiasmatic nucleus (SCN), a site of the circadian pacemaker, is affected by daylength; that is, by the photoperiod. Whereas various markers of rhythmicity have been followed, so far there have been no studies on the effect of the photoperiod on the expression of the clock genes in the rat SCN. To fill the gap and to better understand the photoperiodic modulation of the SCN state, rats were maintained either under a long photoperiod with 16 h of light and 8 h of darkness per day (LD16:8) or under a short LD8:16 photoperiod, and daily profiles of Per1, Cry1, Bmal1 and Clock mRNA in darkness were assessed by in situ hybridization method. The photoperiod affected phase, waveform, and amplitude of the rhythmic gene expression as well as phase relationship between their profiles. Under the long period, the interval of elevated Per1 mRNA lasted for a longer and that of elevated Bmal1 mRNA for a shorter time than under the short photoperiod. Under both photoperiods, the morning and the daytime Per1 and Cry1 mRNA rise as well as the morning Bmal1 mRNA decline were closely linked to the morning light onset. Amplitude of Per1, Cry1, and Bmal1 mRNA rhythms was larger under the short than under the long photoperiod. Also, under the short photoperiod, the daily Clock mRNA profile exhibited a significant rhythm. Altogether, the data indicate that the whole complex molecular clockwork in the rat SCN is photoperiod dependent and hence may differ according to the season of the year.
Keywords: cirkadiánní proteiny Period; Receptors, G-Protein-Coupled; transkripční faktory bHLH; hybridizace in situ; Drosophila Proteins; RNA, Messenger; CLOCK Proteins; fotoperioda; Male; proteiny Drosophily; Rats, Wistar; ARNTL Transcription Factors; Basic Helix-Loop-Helix Transcription Factors; transkripční faktory ARNTL; Photoperiod; oční proteiny; In Situ Hybridization; jaderné proteiny; imunohistochemie; mužské pohlaví; Suprachiasmatic Nucleus; Photoreceptor Cells, Invertebrate; potkani Wistar; Flavoproteins; cirkadiánní rytmus; Circadian Rhythm; proteiny buněčného cyklu; krysa rodu Rattus; trans-aktivátory; Animals; kryptochromy; Transcription Factors; Immunohistochemistry; nucleus suprachiasmaticus; transkripční faktory; Cryptochromes; Period Circadian Proteins; zvířata; Eye Proteins; Rats; receptory spřažené s G-proteiny; fotoreceptory bezobratlých; Trans-Activators; proteiny CLOCK; Cell Cycle Proteins; Nuclear Proteins; messenger RNA; flavoproteiny